Micropropagation of the wild legume Canavalia rosea (Sw.) DC. from coastal sand dunes - D'Cunha, Melwyn; Sridhar, Kandikere (Biological Letters, 2011)
The wild legume Canavalia rosea (known in India as C. maritima) grows on coastal sand dunes of Southwest India. Anthers and 8 other explant types of this species (tender pods, cotyledons of ripened beans, cotyledons of germinated dry seeds, hypocotyls, young shoot buds, nodes, internodes, and roots) were used for in vitro culture. Among them, cotyledons and hypocotyls of germinated dry seeds showed a positive response. Friable callus production was seen within 4 weeks at the cut ends of cotyledon explants in MS medium fortifed with 1 mg L-1 each of BAP and 2iP. Cotyledon explants of seedlings also showed shoot bud induction in MS medium with 0.5 mg L-1 each of BAP and 2iP. Increased shoot bud induction was seen at elevated concentrations of hormones (7-27%). Hypocotyls inserted upside down on the medium with 1 mg L-1 each of BAP and 2iP, gave rise to leafy shoots within 4 weeks. Solitary or multiple somatic embryos emerged from the 10 week-old calli of cotyledons supplemented with 1.5 mg L-1 each of BAP and 2iP. Secondary embryos were also induced in some of the somatic embryos. Hypocotyls excised from 3-5-day-old seedlings in MS medium at low concentrations of auxins, produced roots within 3 weeks. The stem cuttings treated with IBA (0.25 mg L-1) increased the percentage of rooting response. Conventional methods of propagation of C. rosea through seeds may fail due to seed dormancy and mortality of the seedlings under the hostile conditions of coastal sand dunes, thus in vitro and ex vitro culture and hardening techniques may be feasible for rehabilitation. Moreover, such cultured tissues may serve for extraction of secondary metabolites.